2021
DOI: 10.1002/slct.202103243
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Hetareno[e]pyrrole‐2,3‐diones with Thiols: An Approach to Two Distinct 5‐Thio‐Substituted Pyrrole‐2‐one Derivatives

Abstract: Recently, 3‐hydroxy‐1,5‐dihydro‐2H‐pyrrol‐2‐ones have become an object of close scrutiny in medicinal chemistry due to their diverse biological activity. In the present paper, we describe a substrate‐switchable reaction of hetareno[e]pyrrole‐2,3‐diones with aromatic and aliphatic thiols that afforded two series of novel 5‐thio‐substituted 3‐hydroxy‐1,5‐dihydro‐2H‐pyrrol‐2‐ones. The reaction of pyrroloquinaxolinetriones with thiols led to the formation of adducts. The initially formed adducts of pyrrolobenzoxaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The N/S selectivity of o-aminothiophenol towards distinct electrophilic centers is consistent with literature data on reactions of hetareno[e]pyrrole-2,3-diones with amines [10] and mercaptans [28] and can be explained by the HSAB theory. According to this theory, the α,β-unsaturated carbonyl compounds have a carbonyl carbon (hard electrophilic center) and a β-carbon (soft electrophilic center).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The N/S selectivity of o-aminothiophenol towards distinct electrophilic centers is consistent with literature data on reactions of hetareno[e]pyrrole-2,3-diones with amines [10] and mercaptans [28] and can be explained by the HSAB theory. According to this theory, the α,β-unsaturated carbonyl compounds have a carbonyl carbon (hard electrophilic center) and a β-carbon (soft electrophilic center).…”
Section: Resultssupporting
confidence: 90%
“…Previously, we have shown that aryl mercaptan adducts of substrates 3 are unstable and readily degrade to the starting compounds in solution. [28] Although attack of the less nucleophilic nitrogen atom is less preferred, it can cause almost irreversible opening the pyrrole cycle to form the intermediate I2 (Scheme 5, path B). Further sequential attack of the NH and SH groups on the carbonyl carbon atom of the benzoyl substituent results in a more stable compound 5 a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation